Analysis Of Financial Performance PT. Pusri (Persero) Palembang - Yudistira Yudistira; Zahruddin Hodsay; Diana Widhi Rachmawati (Integrated Journal of Business and Economics (IJBE), 2020)
This research is titled financial performance analysis P.T Pusri (persero) Palembang, this research has a purpose for assessing the financial performance of  PT. Pusri (Persero) Palembang when viewed from the ratio calculation. In collecting the data the unstructured documentation and interview method is used. While the analysis techniques used for this study are the liquidity ratio (Current Ratio, Quick Ratio), profitability ratio (Net Profit Margin, Return On Investment, Return On Equity) and activity ratio (Total Asset Turnover, Fixed Asset Turn Over). The report used is the financial statements of  PT. Pusri (Persero) Palembang in 2016-2018. According to the calculations carried out, the results are as follows, The performance of  PT Pusri (Persero) Palembang in 2016-2018 is seen from the liquidity ratio experiencing an increase and the results are liquid, although in a liquid condition the conditions are not good, especially in 2016 and 2017 because they are under industry standard. And for the financial performance of PT Pusri (Persero) Palembang in 2016-2018 seen from the profitability ratio has decreased and in unfavorable conditions because it is below the industry standard because the price of goods in the company is low this can be understood because companies, especially PT Pusri ( Persero) Palembang is a state-owned company under the auspices of SOEs so that this company receives subsidies from the government. While the company's financial performance in 2016-2018 is seen from the ratio of activities experiencing improvement but at a less favorable condition because it is below the industry standard.